Studi Perbandingan Status Kenegaraan Umat Muslim dalam Pelayanan Pendidikan di Inggris dan Jerman - Saputra, Dian; Sassi , Komarudin (STAI Yogyakarta, 2024)
The increasing number of Muslim communities in Europe, especially in the UK and Germany, has highlighted the important role of education in the process of social integration. Inclusive and adaptive education policies can help create equality of opportunity for Muslims and support social cohesion. However, the approach to education policy in the UK and Germany shows significant differences that reflect the history, politics, and culture of each country. This study aims to conduct a comparative study between education policies in the two countries in the context of education services for Muslims. This study is a qualitative study using a literature study approach which will then describe and compare education policies in the two countries in the context of education services for Muslims. By collecting and analyzing data from various sources, including academic journal articles, books, official government reports, and publications from international organizations. The results of the study show that the UK has a more centralized and flexible education policy, allowing support for faith-based schools, including Islamic schools. On the other hand, the decentralized education system in Germany results in variations in policies between states, creating differences in access and implementation of Islamic religious education. Keywords: education, Muslims, education policy, England, Germany